2000
DOI: 10.1007/s002640000134
|View full text |Cite
|
Sign up to set email alerts
|

Early excision of the radial head for fracture

Abstract: The wrists and elbows of 23 patients were examined at a mean follow-up of 5 years (2-10 years) after excision of the radial head for an isolated fracture. Fourteen elbows and 13 wrists were symptomatic. Proximal migration of the radius was seen in 15 cases; the mean distance of migration being 1.4 mm. Osteoarthritis, mostly mild, was seen in 17 elbows and 14 wrists and limited movement of the elbow was a common finding. Excision of the radial head for fracture had a high complication rate.Résumé Le poignet et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 19 publications
2
21
0
3
Order By: Relevance
“…We favor resection over reconstruction in severely comminuted radial head fractures where anatomical fixation cannot be achieved. This is in accordance with multiple studies which concluded that resection of radial head provided satisfactory pain relief and functional range of motion [17][18][19][20][21][22][23]. In our study 80% patients returned to their previous occupation regardless of procedure done.…”
Section: Discussionsupporting
confidence: 93%
“…We favor resection over reconstruction in severely comminuted radial head fractures where anatomical fixation cannot be achieved. This is in accordance with multiple studies which concluded that resection of radial head provided satisfactory pain relief and functional range of motion [17][18][19][20][21][22][23]. In our study 80% patients returned to their previous occupation regardless of procedure done.…”
Section: Discussionsupporting
confidence: 93%
“…1,11,20 A number of clinical studies have documented a high incidence of arthritis following radial head excision which, although not reported to date, can also be expected following excision of the capitellum. 12,[14][15][16] Some weaknesses exist in this study. The sample size was small (n ¼ 8), but it was enough to detect major changes in kinematics between excisions.…”
Section: Discussionmentioning
confidence: 93%
“…Excision of the radial head for fracture has a high complication rate [10]. Several significant complications are associated with radial head excision such as symptoms at the wrist, increased elbow valgus, degenerative arthritis, and so on [2].…”
Section: Introductionmentioning
confidence: 99%